2014
DOI: 10.2478/s11534-014-0487-2
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Droplet as a model for the rotation curve problem

Abstract: Abstract:The dynamics of large scale gravitational structures like galaxies, local groups and clusters is studied based on the so-called Liquid-Droplet model describing the saturation property of the nuclear force. Using the assumption that the gravitational force is also saturated over large scale structures, it is argued that the Newtonian gravitational potential may be replaced by an effective Machian gravitational potential. Application of this new potential at these large scale structures may give the rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Studies with smaller datasets of galaxies showed nonrandom spin directions of galaxies in filaments of the cosmic web [48,95,96]. Other studies showed alignment in the spin directions even when the galaxies are too far from each other to interact gravitationally [49,50], unless assuming modified Newtonian dynamics (MOND) gravity models that explain longer gravitational span [97][98][99]. It should be mentioned that the physics of galaxy rotation is still not fully understood, and it is still not clear why and how galaxies spin.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with smaller datasets of galaxies showed nonrandom spin directions of galaxies in filaments of the cosmic web [48,95,96]. Other studies showed alignment in the spin directions even when the galaxies are too far from each other to interact gravitationally [49,50], unless assuming modified Newtonian dynamics (MOND) gravity models that explain longer gravitational span [97][98][99]. It should be mentioned that the physics of galaxy rotation is still not fully understood, and it is still not clear why and how galaxies spin.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with smaller datasets of galaxies showed nonrandom spin directions of galaxies in filaments of the cosmic web, as described in Tempel and Libeskind, 2013;Tempel et al, 2014;Dubois et al, 2014;Kraljic et al, 2021) and others. Other studies showed alignment in the spin directions even when the galaxies are too far from each other to interact gravitationally (Lee et al, 2019a,b), unless assuming modified Newtonian dynamics (MOND) gravity models that explain longer gravitational span (Sanders, 2003;Darabi, 2014;Amendola et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with smaller datasets of galaxies showed non-random spin directions of galaxies in filaments of the cosmic web Tempel and Libeskind, 2013;Kraljic et al, 2021). Other studies showed alignment in the spin directions even when the galaxies are too far from each other to interact gravitationally (Lee et al, 2019a,b), unless assuming modified Newtonian dynamics (MOND) gravity models that explain longer gravitational span (Sanders, 2003;Darabi, 2014;Amendola et al, 2020). It should be mentioned that the physics of galaxy rotation is still not fully understood, and it is still not clear why and how galaxies spin.…”
Section: Discussionmentioning
confidence: 99%